2021
DOI: 10.1039/d1ma00155h
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic approach to achieving the high thermoelectric performance of La-doped SnTe using resonance state and partial band convergence

Abstract: SnTe is an alternate variant of PbTe possessing an analogous valence band(VB) pattern. However, SnTe exhibits low thermoelectric(TE) efficiency due to Sn defects triggering very high carrier concentration (n). Thus,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…The measured carrier concentration of γ-GeSe was comparable to other highly doped materials. 18,19,38 We note that this experimental result is in contrast to previous first-principles calculations, which showed that bulk γ-GeSe is a semiconductor with a bandgap of approximately 0.4 eV. 33 Figure 2d shows that the hole mobility is 12.2 cm 2 /(V s) at room temperature.…”
contrasting
confidence: 73%
See 4 more Smart Citations
“…The measured carrier concentration of γ-GeSe was comparable to other highly doped materials. 18,19,38 We note that this experimental result is in contrast to previous first-principles calculations, which showed that bulk γ-GeSe is a semiconductor with a bandgap of approximately 0.4 eV. 33 Figure 2d shows that the hole mobility is 12.2 cm 2 /(V s) at room temperature.…”
contrasting
confidence: 73%
“…Figure c shows the thermoelectric power factor (PF = σ S 2 ) at various temperatures below 500 K. At room temperature, γ-GeSe exhibited a power factor of approximately 66.7 μW/(m K 2 ). Figure d shows a comparison of the room-temperature Seebeck coefficient and power factor of γ-GeSe with those of other group IV monochalcogenides. ,,,, The thermoelectric power factor of γ-GeSe is comparable to that of other group IV compounds. Interestingly, the Seebeck coefficient of γ-GeSe is similar to those of GeTe and SnTe but significantly different from those of other Se- or S-based monochalcogenides such as α-GeSe.…”
mentioning
confidence: 90%
See 3 more Smart Citations